KAJIAN PENULISAN TUGAS AKHIR MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JAWA FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI YOGYAKARTA - - Suharti; Endang Nurhayati; Venny Indria Ekowati; Hartanto Utomo (JURNAL IKADBUDI, 2016)
This study is proposed for eight months. The purposes of the study are: (1) identifying the fields of science and sub-fields of research science in the thesis or "Tugas Akhir Skripsi" (TAS) of Javanese Department Students in Faculty of Language and Arts, Yogyakarta State University, (2) identifying the reason for choosing a title, (3) identifying the criteria of thesis supervisor according to the students and alumni of the Javanese Department in Faculty of Language and Arts, Yogyakarta State University, (4) identifying suggestions and criticism from the students and alumni of Javanese Department in Faculty of Language and Arts, Yogyakarta State University related to "TAS". The outcomes of the study are: (1) the data base regarding to the fields of science and sub-fields of research science in "TAS" of Javanese Department students of Faculty of Language and Arts, Yogyakarta State University, (2) reasons for choosing a title, (3) criteria of ideal thesis supervisors according to the students and alumni of Javanese Department in Faculty of Language and Arts, Yogyakarta State University, (4) suggestions and criticism of the students and alumni of Javanese Department in Faculty of Language and Arts, Yogyakarta State University related to "TAS", and (5) a national seminar papers and journals that are not accredited. This study is a survey research using descriptive method with 100 students as the respondents. Based on the findings of the discussion, it can be concluded that: (1) the fields of linguistics as well as the sub-fields of morphology is a field of research the most studied by the students of Javanese Department, (2) reason for choosing a title and topic of thesis by the students is because the students are glad to the field of science and topic taken, (3) the main criteria of the ideal supervisor according to the students of Javanese Department is the appropriateness between the supervisors' field of science and the thesis that is done by the students, (4) respondents noted that they do not agree if the topic and thesis titles are chosen by the Department because of the diversity of the students ability.Keywords: thesis, Javanese Department AbstrakPenelitianini bertujuan untuk: (1) Mengindentifikasi bidang ilmu dan sub bidang ilmu penelitian dalam Tugas Akhir Skripsi (TAS) mahasiswa Program Studi Pendidikan Bahasa Jawa FBS UNY, (2) Mengidentifikasi alasan pemilihan judul, (3) Identifikasi kriteria ideal pembimbing skripsi menurut mahasiswa dan alumni Prodi Pendidikan Bahasa Jawa FBS UNY, (4) Mengidentifikasi saran dan kritik mahasiswa serta alumni Prodi Pendidikan Bahasa Jawa FBS UNY terkait TAS. Jenis penelitian ini adalah penelitian survey dengan metode deskriptif dengan jumlah responden 100 orang mahasiswa maupun alumni Prodi Pendidikan Bahasa Jawa FBS UNY. Penelitian ini menggunakan metode survey. Berdasarkan hasil pembahasan dapat disimpulkan bahwa: (1) Bidang ilmu linguistik serta sub bidang morfologi merupakan bidang penelitian yang paling banyak dikaji, (2) Alasan pemilihan judul dan topik skripsi adalah karena mahasiswa senang terhadap bidang ilmu dan topik yang diambil, (3) Kriteria utama seorang pembimbing yang ideal adalah kesesuaian bidang ilmu pembimbing dengan skripsi yang dikerjakan, (4) Responden menyatakan tidak setuju jika topik dan judul skripsi dipilihkan oleh prodi dengan alasan utama keberagaman kemampuan mahasiswa.Kata kunci: tugas akhir skripsi, Prodi Pendidikan Bahasa Jawa, FBS UNY